(untitled) (Fiep Bulletin - online, 2019)
The article has the theme obesity in schoolchildren, indicating the program of hydrogymnastics as a formof physical activity. Obesity at present affects all age groups and large numbers of people in the world population. The objective ofthe study was to research on obesity and physical activities of water aerobics that can collaborate with schoolchildren regardingthe better quality of life. The methodology and action strategies used were exploratory and bibliographic research. The resultsindicate that obesity is really worrisome and physical activity in an aqua-gymnastics program can help reduce body mass andhelp comorbidities not occur, improving quality of life. The final considerations indicate that the practice of physical exercise inhydrogymnastics prevents diseases that occur when there is excess body mass, causing the BMI to reduce. In this practice thephysical activities, collaborate with the aerobic physical conditioning, important for the activities of several mechanisms of thehuman being.